IMPACT OF COUNTRY OF ORIGIN EFFECT (COE) ON CONSUMER PURCHASE INTENTIONS: A CASE STUDY OF COSMETIC PRODUCTS IN LAMPANG, THAILAND - Pandey, Janak; Muenkid, Somjai; Jivasantikarn, Noraset; Chaisiriwongsuk, Arunie Jivasantikarn; Inthaklhan, Yadarat (ASEAN Marketing Journal, 2021)
Country-of – origin plays an important role in international marketing by creating access to new and bigger markets for organizations globally. Various companies are investing and venturing in overseas market as they would be able to attract and benefit from a larger market share and advantage from economies of scales. This research studies the Country of Origin Effect (COE) and its impact on Consumer Purchase Intentions in Lampang Province, Thailand. For this study, mixed method approach was used combining quantitative and qualitative analysis and both primary and secondary data were analyzed to understand the country of origin effect. This study is done by employing mixed method concept, combining both qualitative and quantitative methods. Data were obtained by two mediums: (a) Quantitative data collection through questionnaires distributed to 120 consumers, (b) qualitative data by conducting face-to-face interview with 20 respondents ranging from different sectors through snowball technique. Result reveal that halo effect, materialism, and value consciousness influeneces consumer purchase intention to buying foreign made cosmetic product. It was found that consumer animosity and consumer ethnocentrism does not influence consumer purchase intetion to buying foreign made cosmetic product. This research will enable entrepreneurs and business organization to have a better understanding about the country-of-origin effects and its perception on end consumers of cosmetic products. The study further gives an insight on the effect of a country’s image on the consumers’ purchase intentions. With influx of ecommerce websites and changing global scenario, it has been become even more important to investigate the above topic so as to be able understand and provide details about country-of-origin effect on consumer purchasing intentions.